Laparoscopic resection of two peritoneal loose bodies on the rectosigmoid colon - Honda, Ken-ichi; Nakagawa, Tomoko; Kurihara, Yasushi; Kajitani, Koji; Ando, Tetsuji; Tendo, Masashige; Takase, Aki; Hamuro, Akihiro (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Laparoscopic examination of a 77-year-old woman revealed two peritoneal loose bodies connected to fatty appendices on the rectosigmoid colon and resected at the stalks. The peritoneal loose bodies were found to be fat-containing masses on preoperative magnetic resonance imaging, and postoperative pathological examination revealed fat degeneration tissue with or without fibrous outer layers.